UMP welcomes 2104 new students - UMP, PNC (2018)
Kuantan, 2 September – A total of 2104 new students registered for degree in this 2018/2019 academic session. Registration took place at both University Sports Complex in UMP Gambang and at Student Activity Centre in UMP Pekan Campus. Earlier, 36 international students from United Kingdom, Yemen, Somalia, Egypt, Bangladesh, Syria, UAE, China and Tanzania registered to pursue their study in UMP.